2001
DOI: 10.1536/jhj.42.79
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Cavotricuspid Isthmus Catheter Ablation on Paroxysmal Atrial Fibrillation

Abstract: SUMMARYIt has been demonstrated that successful cavotricuspid isthmus ablation of typical atrial flutter combined with atrial fibrillation (AF) sometimes influences the preablation history of paroxysmal AF. However, the effectiveness of only isthmus ablation on AF itself is unclear.Endocardial catheter mapping during induced AF was performed around the tricuspid annulus using duodecapolar electrode catheters in 39 patients with drug-refractory paroxysmal AF. Isthmus ablation was performed in 16 patients (41%) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…This suggests that AFL may have been responsible for some episodes of AF. Consistent with a facilitatory role of typical AFL in the pathogenesis of AF, several prior studies have demonstrated that the incidence of AF may be lower after ablation of the cavo-tricuspid isthmus (17)(18)(19)(20). However, in none of these prior studies was the role of PV isolation assessed.…”
Section: Cavo-tricuspid Isthmus Ablation and Recurrence Of Afmentioning
confidence: 71%
“…This suggests that AFL may have been responsible for some episodes of AF. Consistent with a facilitatory role of typical AFL in the pathogenesis of AF, several prior studies have demonstrated that the incidence of AF may be lower after ablation of the cavo-tricuspid isthmus (17)(18)(19)(20). However, in none of these prior studies was the role of PV isolation assessed.…”
Section: Cavo-tricuspid Isthmus Ablation and Recurrence Of Afmentioning
confidence: 71%
“…Typical atrial flutter also easily disorganizes into AF because atrial flutter with a short cycle length may transition to fibrillatory conduction (14). Therefore, CTI ablation may reduce AF recurrence by preventing the organization of AF into atrial flutter, which disrupts AF maintenance (5,(15)(16)(17). Finally, linear ablation of the CTI may have affected the right atrial ganglionated plexus.…”
Section: Mechanismsmentioning
confidence: 99%
“…Several studies have reported that successful AFL ablation decreased the AF recurrence in 50-75% of patients with a history of AF (25)(26)(27)(28)(29)(30)(31)(32)(33). One meta-analysis also demonstrated that the recurrence of AF was 52.7% in patients which a history of AF after a mean of 16 months following period (34).…”
Section: Impact Of Afmentioning
confidence: 99%